Practical infection control training for Victoria’s aged care workforce at the time of COVID-19 pandemic: a community case study - Dix, Samantha; Rawson, Helen; Russo, Philip; Team, Victoria; Griffiths, Debra; Morphet, Julia (Frontiers in Public Health, 2023)
The need to improve career development and training for residential aged care workers in Australia to achieve required essential competencies, including infection prevention and control competencies, has been repeatedly highlighted. In Australia long-term care settings for older adults are known as residential aged care facilities (RACFs). The COVID-19 pandemic has brought to light the lack of preparedness of the aged care sector to respond to emergencies, and the urgent need to improve the infection prevention and control training in residential aged care facilities. The government in the Australian State of Victoria allocated funds to support older Australians in RACFs, including funds toward infection prevention and control training of RACF staff. The School of Nursing and Midwifery at Monash University addressed some of these challenges in delivering an education program on effective infection prevention and control practices to the RACF workforce in Victoria, Australia. This was the largest state-funded program delivered to RACF workers to date in the State of Victoria. The aim of this paper is to provide a community case study, where we share our experience of program planning and implementation during early stages of the COVID-19 pandemic and lessons learned.